Pengaruh Gaya Kepemimpinan, Budaya Kerja dan Motivasi terhadap Produktivitas Kerja Karyawan Hotel Swiss-Bel Balikpapan - Marlindawaty, Marlindawaty; Herwanto, Yudi (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
The research aims to determine the influence of leadership style, work culture and motivation on work productivity especially employees in the Housekeeping Department of the Swiss-Bel Hotel of Balikpapan. This research uses a quantitative approach by distributing questionnaires to 35 employees who were determined using the saturated sampling method. The data analysis method uses SPSS 26.0 tools by carrying out validity, reliability, multiple linear regression analysis and simultaneous and partial hypothesis testing. The results prove simultaneously and partially that leadership style, work culture and motivation have a positive and significant effect on employee work productivity in the Housekeeping Department of the Swiss-Bel Hotel of Balikpapan.